Contribution of Series Resistance in Modelling of High-Temperature Type II Superlattice p-i-n Photodiodes. (19th November 2012) - Wróbel, Jarosław; Martyniuk, Piotr; Rogalski, Antoni
Abstract : We analyze some of the consequences of omitting series resistance in InAs/GaSb p-i-n T2SL photodiode dark current modelling, using simplified p-n junction model. Our considerations are limited to generation-recombination and diffusion-effective carrier lifetimes to show the possible scale of over- or underestimating photodiodes parameters in high-temperature region. As is shown, incorrect series resistance value might cause discrepancies inτ gr andτ diff 's estimations over one order of magnitude.